2015
DOI: 10.3892/ol.2015.2894
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of ERCC1 and ERCC2 gene variants in osteosarcoma, colorectal and breast cancer

Abstract: The Asn118Asn (rs11615) variant in the ERCC1 gene, and the Lys751Gln (rs13181) and Asp312Asn (rs1799793) variants in the ERCC2 gene have been associated with the development of varied types of cancer. The aim of the present study was to test for any association between the ERCC1 and ERCC2 gene variants and three different types of cancer in Mexican-mestizo patients. Patients and their respective controls were formed into three groups: The osteosarcoma group, with 28 patients and 97 controls; the colorectal gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…Our findings revealed an association of ERCC2 -rs1799793/AA genotype with increased risk of BC. These results are corroborated by previous studies in various populations, such as Russians, Mexicans, Chinese, Egyptian, and Taiwanese [ 17 , 30 33 ]. However, the results were not unanimous as other studies of this SNP failed to find positive correlation with BC, especially among Caucasians as well as North American, European sub-populations, Chinese, Portuguese, Poland and Australian [ 9 , 34 39 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings revealed an association of ERCC2 -rs1799793/AA genotype with increased risk of BC. These results are corroborated by previous studies in various populations, such as Russians, Mexicans, Chinese, Egyptian, and Taiwanese [ 17 , 30 33 ]. However, the results were not unanimous as other studies of this SNP failed to find positive correlation with BC, especially among Caucasians as well as North American, European sub-populations, Chinese, Portuguese, Poland and Australian [ 9 , 34 39 ].…”
Section: Discussionsupporting
confidence: 91%
“…It is well known that the DNA repair ability is an important determinant of the predisposition toward various malignancies [ 9 , 24 , 25 ]. There is increasing data supporting the hypothesis that genetic polymorphisms (SNPs) in DNA repair genes could lead to disorder in DNA repair machinery resulting in accumulation of mutations, and in turn could contribute to increased susceptibility to various types of cancers including BC [ 17 , 25 – 27 ]. In particular, the functional SNPs ERCC2 -rs1799793 and ERCC2 -rs13181 enrolled in our study have been previously associated with specific DNA defects, namely defective repair capacity of ultraviolet light-induced DNA damage [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 449 articles were reviewed, and eventually 86 articles with 38,848 cases and 48,928 controls met the inclusion criteria. Among these publications, there was 1 osteosarcoma [ 23 ], 1 hepatocellular cancer (HCC) [ 24 ], 3 oral cancer [ 25 27 ], 5 skin cancer [ 28 32 ], 5 colorectal cancer [ 23 , 33 36 ], 6 head and neck cancer [ 37 42 ], 6 esophageal cancer [ 43 48 ], 6 non-Hodgkin lymphoma [ 49 54 ], 6 prostate cancer [ 55 60 ], 8 gastric cancer [ 61 – 67 ], 12 bladder cancer [ 68 79 ], 14 lung cancer [ 70 , 80 92 ], and 15 breast cancer [ 23 , 32 , 93 105 ]. The detailed study selection process is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Wu et al indicated that the ERCC2 Asp312Asn polymorphism was not associated with the development of HCC [ 24 ]. Gomez-Diaz et al demonstrated no relationship between ERCC2 Asp312Asn polymorphism and osteosarcoma [ 23 ]. Interestingly, based on a study by Mahimkar et al this polymorphism was associated with an overall increase in chromosomal damage in oral cancer [ 25 ].…”
Section: Discussionmentioning
confidence: 99%